The degree Contribution of Psychological Counselor in Enhancing the National belonging among students second cycle of basic education Afield Study in Lattakia Governorate Dr. Rola Reda Shriki - شريقي , رولا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to identify the degree of contribution of Psychological Counselor in Enhancing the National belonging among students second cycle of basic education in Lattakia Governorate from the point view of Schools Managers and their Assistants in Lattakia Governorate, also to identify the differences between the answers of the research sample according to the following variables: (scientific and educational qualification, years of experience). To achieve the objectives of this research, a questionnaire was built, consisted of (62) paragraph, has been applied on a sample of (116) Managers and their Assistants, during the academic year (2020 - 2021), and used Descriptive method, also to approve the questionnaire validity, it was showed to a jury of (7) of specialized adjudicators in Faculty of Education at Tishreen and Tartous Universities. Its constancy was assured by applying it on a sample consisted of (22) Managers and their Assistants in Lattakia Governorate through Cronbach – Alpha Reliability (0.903), and (0.955) at Spearman-Brown, which indicate to high reliability to questionnaire. The research concluded the following results: The degree contribution of psychological counselor in enhancing the national belonging among students second cycle of basic education in Lattakia governorate was middle degree. There were differences of statistical indication between the sample research of Managers and their Assistants about the degree of contribution of psychological counselor in enhancing the national belonging among students according to the variable scientific and educational qualification in favor of holding Education Preparation Diploma, but there were no differences of statistical indication according to the variable years of experience. The research recommended intensifying the interest in the Psychological Counselors, and prepare him scientifically, academically, professionally, and inculcating the values of belonging, participation and work among students, also adopting advanced methods to consolidate the values of belonging among students in the different stages of education.